A Function-Oriented Analysis of Prophet Name Translation in Abdel Haleem’s ‘The Quran: A New Translation - Muhammad Nur; Novriyanto Napu; Magdalena Baga (TRANSBAHASA, 2024)
The translation of prophets' names in the Quran often differs from their original form, with English translations frequently aligning more closely with the biblical figures. This raises the question of whether these translations still accurately reflect the Quranic depiction of the prophets. This study aims to examine the translation strategies applied by M.A.S. Abdel Haleem in translating the names of the twenty-five prophets in his 2004 English rendition of the Quran and how these translations maintain the intended meaning. The research employs a 'Function-Oriented' translation approach, which focuses on the socio-cultural function of translation within the recipient's context. Using Hermans' (1988) four strategies for translating proper names—pure borrowing, naturalization, adaptation, and literal translation—Abdel Haleem applies the naturalized strategy to nine prophet names and the adaptation strategy to sixteen names. These strategies enable the translation to remain culturally appropriate and intelligible for the target audience while still representing the Quranic names. The study highlights the cultural challenges inherent in translation, as understanding the names depends on the target culture, necessitating a shared cultural understanding between the translator and reader. This research contributes to translation practices by emphasizing the importance of balancing linguistic fidelity and cultural adaptation in religious texts.